The Paramount Hotel, Freetown: Neocolonial Investment and the Business of Tropical Modernism in Sierra Leone - Ewan Harrison (ABE Journal)
This article examines the planning of the Paramount Hotel in Sierra Leone, completed to the designs of James Cubitt & Partners in 1961, during Sierra Leone’s transition from colonial rule to independence. This paper demonstrates that the hotel was conceived of as a neocolonial instrument planned and funded by the British government’s Colonial Development Corporation to support the continued operation of British capital in a post-imperial world. At the same time, tourist-based development was a central component of economic planning in the immediate post-independence years for Sierra Leone’s political class. This paper therefore reveals that the luxury hotel played a central, if unstable, role in planning for economic futures during the ends of empire in Sierra Leone.